Implementasi Program “Santun Lansia” Puskesmas Kabupaten Sleman - Ruliyandari, Rochana (Universitas Ahmad Dahlan, 2018)
Background: The elderly courtship program is a manifestation of the concern of the Sleman District Government to the elderly people who need special services because of their old physical structure, where the elderly have the same right to continuously improve their health so that they remain capable and active in the development, productive socially and economically. Method: The type of this research is descriptive by analyzing data of elderly program. The elderly data is obtained from the coverage report of puskesmas services, laws and regulations related to this issue and criteria of elderly mannered programs. Results: the elderly polite program is the government policy of Sleman Regency seen from the program facilities owned to the number of visits of elderly patients who receive health services. The total number of elderly in Sleman regency is 105.955 people. Primary Health Center (Puskesmas) visitors with strata I as many as 9,892 people, 2 Puskesmas with strata II amounted to 62,579. Primary Health Center (Puskesmas) with strata III amounted to 9,192 people and primary health center strata IV not yet exist in Sleman Regency. Conclusion: The elderly decentralized program refers to government policies that are set forth in laws and regulations. Continuous evaluation is required to improve the infrastructure and services of puskesmas in order for the elderly to obtain the same comfort as the general patient.